2006
DOI: 10.1007/s11084-006-9022-9
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Path to the RNA World: Enantioselective and Diastereoselective Purification of Ribose

Abstract: A theoretical mechanism resulting in the prebiotic appearance of enantiopure ribose, which would be needed for the origin of RNA and the "RNA world" is proposed. The mechanism simultaneously explains the emergence of biological homochirality and could answer the question of why nucleic acids are based on ribose rather than another sugar. Cleavage of certain non-chiral mineral crystals is known to lead to formation of chiral surfaces. In a chromatography-like process a mixture of racemic carbohydrates originati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Calcite may thus represent a more plausible template than quartz for prebiotic selection and organization of homochiral polypeptides. Similarly, ribose is selectively concentrated on rutile from equimolar solutions of the isomeric pentose sugars: arabinose, lyxose, ribose, and xylose (Hazen 2006;Bielski and Tencer 2006;Cleaves et al 2009). Additional competitive adsorption experiments, including studies that incorporate realistic sea water salinity, are needed, even though divalent cations in solution may inhibit molecular self-organization in some systems (Monnard et al 2002).…”
Section: Opportunities In Mineral Surfaces Researchmentioning
confidence: 99%
“…Calcite may thus represent a more plausible template than quartz for prebiotic selection and organization of homochiral polypeptides. Similarly, ribose is selectively concentrated on rutile from equimolar solutions of the isomeric pentose sugars: arabinose, lyxose, ribose, and xylose (Hazen 2006;Bielski and Tencer 2006;Cleaves et al 2009). Additional competitive adsorption experiments, including studies that incorporate realistic sea water salinity, are needed, even though divalent cations in solution may inhibit molecular self-organization in some systems (Monnard et al 2002).…”
Section: Opportunities In Mineral Surfaces Researchmentioning
confidence: 99%
“…the utilization of only particular optical isomers by living organisms, could have begun from the selection of a particular D-isomer of ribose -since nucleobases and phosphate groups are non-chiral [307]. Generally, homochirality cannot be completely explained in the framework of the "primordial soup" concept [3][4][5], because stereoisomers are chemically indistinguishable in a homogenous solution.…”
Section: First Settlers In the Zns Worldmentioning
confidence: 99%
“…Generally, homochirality cannot be completely explained in the framework of the "primordial soup" concept [3][4][5], because stereoisomers are chemically indistinguishable in a homogenous solution. At a surface, however, the properties of two stereoisomers could differ [307], as first pointed out by Goldschmidt, who has suggested that mineral surfaces were involved as templates in abiogenesis [35,308]. The two other tentative mechanisms of primordial stereoselectivity are (i) photoselection by polarized UV light (see [309] and references therein), and (ii) enantiomeric autocatalysis (see [310,311] for reviews).…”
Section: First Settlers In the Zns Worldmentioning
confidence: 99%
“…Let us look now at the resolution of some natural products in the AES [33,34]. It seems that the AES process can be facilitated by the increased number of chiral centers, particularly when they are in the ring.…”
Section: Aes Of Monosaccharidesmentioning
confidence: 99%
“…Nonsubstituted carbohydrates have rarely been chromatographed in a non-reversed phase system. Nevertheless, there are a few reports [33,36] showing that ribose is indeed the slowest (or one of the slowest) monosaccharides when unmodified (non-substituted) sugars are separated using a normal phase chromatography. So far we assumed that adsorption takes place mainly due to the formation of hydrogen bonds.…”
Section: Aes Of Monosaccharidesmentioning
confidence: 99%